Considering Family Dog Attachment Bonds: Do Dog-Parent Attachments Predict Dog-Child Attachment Outcomes in Animal-Assisted Interventions? - Wanser, Shelby H.; Simpson, Amelia Chloe; MacDonald, Megan; Udell, Monique A. R. (Frontiers in Psychology, 2020)
Animal-Assisted Interventions (AAI) have become more prevalent in recent years, with dog-assisted interventions among the most popular. The literature suggests that a variety of dog-human interventions have the potential for beneficial outcomes for human participants and owners, however critical gaps in knowledge still exist. Research addressing intervention outcomes for dogs, and the impact of AAI on the dog-human bond, has lagged behind. Even less is known about how dogs perceive child partners in AAI settings. The current study, which involved AAI for youth with developmental disabilities and their family dog, aimed to determine if the dog’s style of attachment to a primary adult caretaker in the home was predictive of dog-child attachment style pre-and post-intervention. Using a Secure Base Test, the attachment style of the family dog toward an adult owner/parent was evaluated, and the attachment style of the dog toward the participating child was assessed before and after the dog-assisted interventions. The dog’s attachment style to the child was then compared to the dog-parent attachment style. The findings show that all dogs with a secure attachment to the child at the initial assessment also had a secure attachment to the parent. It was also demonstrated that AAI has the potential to change the attachment style between a family dog and child to a more secure attachment, and that the dog-parent attachment style is a significant predictor of which dogs were able to develop a secure attachment to the child over the course of the AAI.